Some Notes on Words Gorurce and Tutarca - Kilic, Gamzegul (ISTANBUL UNIV, 2022)
This article examines the grammatical structure and meaning of the words gorurce and tutarca. The use of these words was notably mentioned as organ names in my master's thesis titled Firuz-i Cihangir Story Language Analysis-Text-Dictionary (Folios 71r-140r). This prose story of Firuz-i Cihangir is an original Persian work on bravery and adventure. It was translated into Turkish in by Celalzade Salih Celebi upon the behest of Suleiman the Magnificent. The words examined in this article, occur in the 3(rd) volume of the work which is found in the Pertevniyal Section of the Suleymaniye Manuscript Library. Upon encountering the two Turkish words mentioned above in the transcription of the text, various texts with the term dictionaries were scanned within the scope of this article. As a result of the research, these words appear to have occurred in Turkish between the 14(th) -21(st) centuries in Turkey, but they were not used for organ names. This article discusses the structure of the words gorurce and tutarca that are formed with a common morpheme (-ArcA/-(I)rcA), by taking into account morphemes with similar functions (-DIkCA, -IncA/-sIncA, -mAcA, -lIcA). The article has identified words derived from this suffix and has attempted to evaluate its functions and meanings.
Keywords: Gorurce; tutarca; organ names; combined suffix; ArcA; -(I)rcA; Firuz-i Cihangir Hikayesi; Linguistics; Literature